2009
DOI: 10.1021/om900090q
|View full text |Cite
|
Sign up to set email alerts
|

Heterobimetallic Cr−Mn Complexes of Fused Arenes: Chromium-Templated Benzannulation of a Cymanthrene-Type Metal Carbene and Haptotropic Metal Migration along a Dibenzo[c,e]indene Platform

Abstract: The chromium-templated benzannulation of the chromium cymanthrene-type carbene 3 with 3-hexyne affords the heterobimetallic chromium−manganese hydroquinoid dibenzo[c,e]indene complexes anti-4 and syn-5, in which the chromium entities are coordinated regioselectively to the hydroquinoid ring. Both diastereomers undergo a thermoinduced haptotropic migration of the chromium moiety to give their haptotropomers anti-6 and syn-7 in comparable yields, independent of the relative configuration of both metal centers, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 88 publications
0
8
0
1
Order By: Relevance
“…This process in which the metal center remains permanently coordinated to the ligand during the metal relocation is referred to as haptotropic metal migration . Since the first report of a reversible shift of a Cr(CO) 3 fragment along the platform of 2,3-dimethylnaphthalene, the rearrangement of chromium fragments along arene platforms has attracted increasing interest. , Experimental and theoretical investigations have been undertaken to elucidate the mechanism of this process. Theoretical studies on naphthalene tricarbonyl chromium complexes suggested a metal shift along the periphery of the π-system via a η 4 -coordinated trimethylene methane-like transition state .…”
Section: Introductionmentioning
confidence: 99%
“…This process in which the metal center remains permanently coordinated to the ligand during the metal relocation is referred to as haptotropic metal migration . Since the first report of a reversible shift of a Cr(CO) 3 fragment along the platform of 2,3-dimethylnaphthalene, the rearrangement of chromium fragments along arene platforms has attracted increasing interest. , Experimental and theoretical investigations have been undertaken to elucidate the mechanism of this process. Theoretical studies on naphthalene tricarbonyl chromium complexes suggested a metal shift along the periphery of the π-system via a η 4 -coordinated trimethylene methane-like transition state .…”
Section: Introductionmentioning
confidence: 99%
“…[22] Although the redox-induced hapticity changes in transition-metal complexes featuring polyaromatic ring systems or tub-to-chair isomerizations in cyclooctatetraene (COT) complexes have been well studied, [18a, 23] the intramolecular migration of a metal fragment between ring systems is rare. [24] ). Remarkably, the intermolecular exchange process was not observed in the reaction between equimolar amounts of ferrocene and [C 4 Ph 4 BPh]K 2 in THF, which suggests that the ligation of the borole moiety prior to reduction is essential.…”
mentioning
confidence: 99%
“…[22] Although the redox-induced hapticity changes in transition-metal complexes featuring polyaromatic ring systems or tub-to-chair isomerizations in cyclooctatetraene (COT) complexes have been well studied, [18a, 23] the intramolecular migration of a metal fragment between ring systems is rare. [24] It appears that the electron-richer [C 4 Ph 4 BR] 2À entity is a better p donor than Cp À , consequently forming a stronger bond with the iron center. Thus, two-electron reduction of 1 gives rise to the formation of the putative [CpFe(h 5 -C 5 H 4 -BC 4 Ph 4 )] 2À species, which then undergoes an intramolecular [CpFe] migration to form [CpFe(h 5 -Ph 4 C 4 B-C 5 H 4 )] 2À ([1] 2À ).…”
mentioning
confidence: 99%
“…With the aim of exploiting metal−metal interactions, heterobimetallic complexes have become a prominent field of organometallic research. , We became interested in whether the chromium migration can be controlled by another metal moiety coordinated to an extended π-platform. Recently, we reported on a chromium shift in binuclear (Cr, Mn) dibenzo[ c , e ]indene complexes . In this paper, we focus on dibenzoquinoline manganese chromium complexes bearing a terminal pyridine ring, which is well-suited for σ-coordination of low-valent transition metals.…”
Section: Introductionmentioning
confidence: 99%